Green tides: the Suez Canal as key hub and green corridor for a hydrogen future between the Middle East and Europe - Tobias Zumbraegel; Alisa Kegel (Frontiers in Energy Research)
The shipping industry faces the dual challenge of reducing emissions to meet net-zero targets by 2050 and transporting green energy sources like hydrogen and its derivatives. Green shipping corridors provide experimental routes for low-carbon solutions, with the Suez Canal uniquely positioned to lead. This paper examines the canal’s evolving role as a dynamic energy space, where diverse actors and networks intersect, shaping spatial power relations and aligning with green capitalism interests. It explores the Suez Canal’s potential to serve as a model for hydrogen initiatives and its capacity to influence global energy governance and geopolitical dynamics in the transition to a sustainable shipping future. The canal also represents a microcosm of broader global shifts toward a future hydrogen economy, where numerous stakeholders vie for power and influence.